Comparison of central vein pressure between distal, medial, and proximal lumens with water manometer method - Cornellius Hendra Purnama Aria Sumantrie; Bambang Pujo Semedi; Bambang Purwanto (Universitas Muhammadiyah Surabaya, 2021)
ABSTRACT Catheter Vein Pressure in ward-cared patients is rarely measured and considered invalid. The two catheter vein pressure postulates contradict, making confusion among health workers. Dr Russo said the distal-medial-proximal Catheter Vein Pressure has no difference but were denied by Susan S. Scott. Proof of postulate is needed as a solution to inward care. Therefore, this study aimed to compare the central vein pressure between distal, medial, and proximal lumens with the water manometer method. Forty-nine samples retrospective study were taken from the distal - medial - proximal Catheter Vein Pressure of the